Multidrug efflux systems in Escherichia coli and Enterobacter cloacae obtained from wholesome broiler carcasses - Moreira, Maria Aparecida S.; Rodrigues, Patrícia P.C.F.; Tomaz, Rafael S.; Moraes, Célia A. de (Brazilian Journal of Microbiology, 2009)
Members of the Enterobacteriaceae family are present in the intestines of man and animals as commensals or are important disease causing agents. Bacteria bearing multidrug efflux systems (MDR) are able to survive adverse ecological niches. Multiresistant Escherichia coli and Enterobacter cloacae isolates from wholesome broiler carcasses were investigated for the presence of MDR. Lowering of Minimal Inhibitory Concentration for antimicrobials in the presence of a proton-motive force (PMF) uncoupler was tested as a potential display of the MDR phenotype. PCR amplification of the genes encoding AcrA and AcrB, components of a MDR system was performed. Diversity of each species was ascertained by Pulsed-Field Gel Electrophoresis (PFGE) of DNA digested with endonuclease XbaI. For all the isolates, except E. coli 1 and E. cloacae 9, lowering of MIC or of the growth rate in the presence of antimicrobials was observed, indicating a PMF dependent resistance mechanism. Expected products of DNA amplification with acrAB derived primers was obtained with all E. coli strains and with two of the five E. cloacae strains. Dendrogram generated shows diverse pulsetypes, confirming the genetic diversity among the strains. An important issue and related public health is the fact that different models and mechanisms of antimicrobial resistance are present in a small number of non-pathogenic strains and isolated from the same origin. These may be sources of resistance genes to others microorganisms, among them, pathogenic strains

Os membros da família Enterobacteriaceae estão presentes no intestino do homem e dos animais como comensais ou agentes causadores de doença importantes. Bactérias multirresistentes podem possuir sistemas de efluxo multidrogas (MDR) sendo capazes de sobreviver em nichos ecológicos adversos. Escherichia coli e Enterobacter cloacae, multirresistentes, isoladas de frangos sadios foram investigadas quanto à presença de MDR. A diminuição da concentração inibitória mínima de antimicrobianos, na presença de um desacoplador da força próton motora (PMF), foi usada para detectar o fenótipo MDR. Foi realizada PCR dos genes codificadores de AcrA e AcrB, componentes de um sistema MDR. A diversidade de cada isolado foi confirmada por eletroforese em gel de campo pulsado (PFGE) usando a endonuclease XbaI. Observou-se em todos os isolados, exceto E. coli 1 e E. cloacae 9, uma diminuição das MICs ou das curvas de crescimento na presença dos antimicrobianos, indicando um mecanismo de resistência dependente da PMF. Os produtos amplificados esperados derivados de acrAB foram obtidos em todos os isolados de E. coli e em dois, dos cinco, de E. cloacae. O dendrograma gerado mostra diferentes perfis de bandas (pulsetypes), confirmando a diversidade genética entre os isolados. Uma questão importante e relacionada à saúde publica é o fato de que diferentes modelos e mecanismos de resistência aos antimicrobianos estão presentes em um número reduzidos de isolados não patogênicos e obtidos de uma mesma origem. Esses podem ser fontes de genes de resistência para outros microorganismos, entre eles, cepas patogênicas
Keywords: Multiresistance; Antimicrobials; Enterobacteriaceae; Proton-motive force; Diversity